Ordinance no. 11—An Ordinance Concerning Offenses and Disorderly Conduct, § 7, Ilwaco Town Council (1891) (Washington). - (:unkn) unknown (General Publisher, 1891)
Any person or persons who shall draw any species of firearms or any dirk, dagger or knife or any other dangerous or deadly weapon upon the person of another within the corporate limits of the Town of Ilwaco, shall upon conviction thereof before the Police Court be fined not less than Twenty ($20) dollars nor more than One Hundred ($100)2 dollars or by imprisonment in the Town jail not less than Ten (10) days nor more than Twentyy (20) days or both at the discretion of the Court...
--
Keywords: BRANDISHING